Answer:
First option: [tex]-\frac{1}{4}+(-\frac{5}{3})[/tex]
Step-by-step explanation:
By definition, Equivalent expressions have the same value, even though they are written in different forms.
For this exercise it is important to remember the multiplication of signs:
[tex](+)(+)=+\\(+)(-)=-\\(-)(-)=+[/tex]
Given the following expression:
[tex]-\frac{1}{4}-\frac{5}{3}[/tex]
Since:
[tex](+)(-)=-[/tex]
You know that:
[tex]-\frac{5}{3}=+(-\frac{5}{3})[/tex]
Therefore, knowing this, you can determine that the given expression can be written in the following form:
[tex]-\frac{1}{4}+(-\frac{5}{3})[/tex]
The equivalent expression is the one shown in the first option.